Implementasi Nilai-Nilai Kepemimpinan Profetik dalam Budaya Pelayanan: Studi Kasus Bank Syariah Indonesia di Nagan Raya - Raihan, Raihan; Ardila, Fitri (Liwaul Dakwah: Jurnal Kajian Dakwah dan Masyarakat Islam, 2025)
This study examines the implementation of Islamic service at Bank Syariah Indonesia (BSI) KCP 2 Alue Bilie, Darul Makmur District, Nagan Raya Regency. The main focus is on how Islamic leadership principles based on the exemplary traits of the Prophet Muhammad PBUH, such as honesty (shiddiq), trustworthiness (amanah), professionalism (fathanah), effective communication (tabligh), patience, and empathy are applied in customer service. The research employs a qualitative descriptive method with in-depth interviews of employees and customers. The findings show that services at BSI are in accordance with Sharia principles and Islamic leadership values despite some technical and customer comprehension challenges. This study highlights the importance of strengthening Islamic values to build a work culture and service that is not only professional but also spiritually and socially valuable.